1977
DOI: 10.1073/pnas.74.10.4288
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus mRNA can be covalently crosslinked via the 5' cap to proteins in initiation complexes.

Abstract: Proteins that are located adjacent to the 5' end of mRNA in initiation complexes have been detected by chemical crosslinking. Reovirus mRNA containing radioactivity exclusively in the [3H]methyl-labeled "cap," m7G(5')ppp(5') GM, was oxidized with sodium periodate to conveit the 2',3'-cis-diol of the 5'-terminal m7G to a reactive dialdehyde. Oxidized mRNA was incubated in cell-free protein-synthesizing systems derived from wheat germ or mammalian cells, and the resulting mRNA-ribosome initiation complexes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(37 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Similarly, a limited and reproducible group of proteins could be crosslinked to the capped end of oxidized reovirus mRNA in initiation complexes fomed in wheat germ extracts (7). In the present study we have tested several additional viral mRNAs and observed that the same proteins interact with the 5'-caps of different mRNAs in initiation complexes.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Similarly, a limited and reproducible group of proteins could be crosslinked to the capped end of oxidized reovirus mRNA in initiation complexes fomed in wheat germ extracts (7). In the present study we have tested several additional viral mRNAs and observed that the same proteins interact with the 5'-caps of different mRNAs in initiation complexes.…”
Section: Introductionmentioning
confidence: 89%
“…Previously we showed that oxidized reovirus mRNA bound to wheat germ or rabbit reticulocyte initiation complexes can be cross-linked by the 5'-cap m G to a limited set of proteins (7). Because reovirus mRNA consists of a mixture of large, medium and small molecules (17) lyzed by SDS-polyacrylamide gel electrophoresis and fluorography (7).…”
Section: '3mentioning
confidence: 99%
See 3 more Smart Citations